The Routledge handbook of contemporary readings on tribe and religions in India (London Routledge, 2025)
Tribal societies in India observe a diverse set of religious practices which are a quintessential part of their community life. This handbook explores rituals, beliefs, ceremonies and festivals, liturgy, knowledge and traditions that tribal people practice today and traces the history of their interaction with other religions, communities and cultures. The book provides analytical, intellectual, and cultural insights into the religious tradition of tribes within the interactive space of a pan-Indian civilisation. It examines contemporary religious practice within tribes while also exploring changes either brought on by interactions or political interventions. The volume reflects on the intersections of cultural or political life of communities and their religious worldviews. The book also discusses the processes of assimilation or adoption of different religion or religious traditions by tribes and the challenges of detribalisation and shrinking populations of vulnerable groups. It explores both established and emerging dynamics in the field of tribe and religion and provides a look into the unique systems of kinship, worship and life within many different tribal communities in India. This and its companion handbook, The Routledge Handbook of Tribe and Religions in India: Contemporary Readings on Spirituality, Belief and Identity, provide a comprehensive look into the religious life and practices of a very diverse group of tribes in India. It will be of interest to academics and researchers working in the fields of religion, anthropology, indigenous and tribal studies, social and cultural anthropology, sociology of culture, sociology of religion, development studies, history, political science, folkloristic, and colonialism.
Keywords: Tribes- India; Tribes- religion- India; Tribes- culture- India